Semantic mediation between ontologies. (1st January 2012) - Hossam, Tamer; Zaki, Mohamed; Badran, Khaled
Mediators describe elements that handle interoperability problems between different web services. A particular type of mediators is the data mediator, which is used to solve the terminological mismatches between ontologies. Ontology is a specification of conceptualisation which represents a key element of Semantic Web Services (SWS). Formally, it specifies the terminology used to describe a SWS functionality and behaviour. When the web services interact with each other and there are some requests needed from these services, the instance data must be translated from terms of a service into terms of the other service which is called instance transformation. This paper presents a design and an implementation of a mediator, to handle interoperability between two different ontologies. Different types of transformation services are presented and several transformation operations are explained in order to enable the mapping process. A new tool is proposed which has a facility to build ontologies with the ability for creating mediators. The proposed mediator can exploit many types of transformation services. The advantages of that mediator over the previous ones are explained and its implementation is investigated.